Genel konfor ölçeğinin Türkçe'ye uyarlanması - (:unkn) unknown (My University, 2008)
Amaç: Katharine Kolcaba tarafından geliştirilen Genel Konfor Ölçeği I GKÖ'nün (General Comfort Questionary I GCQ) geçerlilik ve güvenirlik çalışmalarını yaparak Türkçe'ye uyarlamaktır. Yöntem: Birinci aşamada ölçek Türkçe'ye çevrilmiş, geri çevirisi yapılmış ve uzman görüşüne sunularak kapsam geçerliliği yapılmıştır, ikinci aşamada ölçeğin Türkçe şekli Memnuniyet Ölçeği (Servqual Scale) ile birlikte 190 hastaya uygulanmıştır. Bulgular: Pearson Korelasyon, Cronbach's Alpha analizleri ile inceleme sonucunda ölçeğin yüksek iç tutarlılığa (a=.85) sahip olduğu ve yapı geçerliliğinin ve güvenilirliğinin yeterli olduğu belirlenmiştir. Sonuç: Ölçeğin daha geniş populasyona ve sağlıklı bireylere de uygulanması önerilmiştir.

Objective: The purpose of this study was to assess the validity and reliability of the General Comfort Questionaire ( GCQ ) for the populasyon of Turkey. Method: In the first stage, the questionaire was firstly translated into Turkish and after then was translated back into English by specialists. The content validity was performed by consultants. In the second stage final form of the questionaire and the Servqual Scale were applied on convenience sample of 190 patients . Results: The data which collectedfrom this sample was used in the evaluation of the reliability and validity of the questionaire. Pearson correlation, cronbach alpha coefficient were used to test these characteristics. Conclusion: The instrument had high consistency (a=.85) and its structural validity was satisfactory. Some further studies on sub-grups with different demographic characteristics was recommended in order to refine its validity and reliability.
Turkish version of the general comfort questionaire
Keywords: Hemşirelik